(untitled) (Revista Argentina de Musicología, 2018)
In previous works we have tried to grasp the complex web of meaning existing around one of the most popular musical genres in Cuyo: the cueca cuyana. Among others. we have identified a series of labels that burden the followers of traditional popular music in Cuyo, that have led to the construct ion of a stigmatized identity. This paper attempts a brief inquiry of the construction of the stigmatic label nationalists. In the first place, we will center our analyses in the discourse of the pioneers of mass diffusion of Cuyo musical genres in the l930s. And later on, we will explore the megafestival Argentina en Mendoza, held in that province in the 1990s.